Smith's general urology (London, 1995)
This book provides in a concise format the information necessary for the understanding, diagnosis, and treatment of diseases managed by urologic surgeons.It has been reviewed and updated throughout, with emphasis on current references. The several hundred illustrations have been further madernized and improved, including many fine anatomic drawings and latest imaging techniques
Keywords: genetourinary organs,urology; diseases